2016
DOI: 10.1007/978-1-4939-3673-1_15
|View full text |Cite
|
Sign up to set email alerts
|

A High-Throughput Flow Cytometry Assay for Identification of Inhibitors of 3′,5′-Cyclic Adenosine Monophosphate Efflux

Abstract: Summary Assays to identify small molecule inhibitors of cell transporters have long been used to develop potential therapies for reversing drug resistance in cancer cells. In flow cytometry, these approaches rely on the use of fluorescent substrates of transporters. Compounds which prevent the loss of cell fluorescence have typically been pursued as inhibitors of specific transporters, but further drug development has been largely unsuccessful. One possible reason for this low success rate could be a substanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Several reports have found that the metal chelating effect of clioquinol may be useful in preventing the development of Alzheimer's disease (Billings et al, 2016;Cherny et al, 2001). Several reports have also found that the inhibitory effect of clioquinol on ATP binding cassette subfamily C (ABCC) transporter function may be useful for inhibiting the growth of hematological tumors (McInerney et al, 2018;Perez et al, 2016). Because ABCC4, 5, and 11 are transporters that can be affected by clioquinol, Perez et al analyzed the regional distribution of polymorphisms of the associated genes in the Japanese population (Super Science High School Consortium, 2009) in combination with reports on the residential areas of SMON patients (Kono, 1971) and reported that the ABCC4 rs3765534 and ABCC11 rs17822931 polymorphisms were candidate gene variants associated with the development of SMON (Perez et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have found that the metal chelating effect of clioquinol may be useful in preventing the development of Alzheimer's disease (Billings et al, 2016;Cherny et al, 2001). Several reports have also found that the inhibitory effect of clioquinol on ATP binding cassette subfamily C (ABCC) transporter function may be useful for inhibiting the growth of hematological tumors (McInerney et al, 2018;Perez et al, 2016). Because ABCC4, 5, and 11 are transporters that can be affected by clioquinol, Perez et al analyzed the regional distribution of polymorphisms of the associated genes in the Japanese population (Super Science High School Consortium, 2009) in combination with reports on the residential areas of SMON patients (Kono, 1971) and reported that the ABCC4 rs3765534 and ABCC11 rs17822931 polymorphisms were candidate gene variants associated with the development of SMON (Perez et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Clioquinol was considered a useful medication with strong antibacterial activity during the 1950s and 1960s in Japan. Recently, clioquinol has been suggested for the treatment of neurodegenerative diseases such as Alzheimer's disease (Billings et al, 2016;Cherny et al, 2001) and tumors (McInerney et al, 2018;Perez et al, 2016). Thus, it is essential to analyze the effects of genetic background on clioquinol metabolism before considering the introduction of clioquinol and its analogues in Japan to prevent the recurrence of SMON.…”
Section: Introductionmentioning
confidence: 99%
“…Only recently, ATP transporters were suggested as possible targets. A screen to identify compounds that block active cAMP efflux identified clioquinol ( Perez et al, 2016 ). What makes this class of targets attractive is that several function-modifying polymorphisms are highly present in Japan but not in other geographic areas ( Perez et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%